2019
DOI: 10.1088/1748-605x/ab279d
|View full text |Cite
|
Sign up to set email alerts
|

Application of high resolution DLP stereolithography for fabrication of tricalcium phosphate scaffolds for bone regeneration

Abstract: Bone regeneration requires porous and mechanically stable scaffolds to support tissue integration and angiogenesis, which is essential for bone tissue regeneration. With the advent of additive manufacturing processes, production of complex porous architectures has become feasible. However, a balance has to be sorted between the porous architecture and mechanical stability, which facilitates bone regeneration for load bearing applications. The current study evaluates the use of high resolution digital light pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 77 publications
4
55
0
Order By: Relevance
“…56 Furthermore, β-TCP scaffolds produced by DLP exhibited a Weibull modulus ranging from 3.2 to 7.4 depending on the architectural geometry (eg, grid-like and hexagonal). 20 However, all these calcium phosphate scaffolds had a less porous, ordered structure of parallel/perpendicular rods instead of a highly porous foam-like architecture, like that of the hydroxyapatite scaffolds produced in this work; such a difference could explain the relatively low value of Weibull modulus in the latter case.…”
Section: Resultsmentioning
confidence: 64%
“…56 Furthermore, β-TCP scaffolds produced by DLP exhibited a Weibull modulus ranging from 3.2 to 7.4 depending on the architectural geometry (eg, grid-like and hexagonal). 20 However, all these calcium phosphate scaffolds had a less porous, ordered structure of parallel/perpendicular rods instead of a highly porous foam-like architecture, like that of the hydroxyapatite scaffolds produced in this work; such a difference could explain the relatively low value of Weibull modulus in the latter case.…”
Section: Resultsmentioning
confidence: 64%
“…Unlike FDM-based 3D printers, the DLP-type 3D printing system used herein reduces the processing time by conducting the simultaneous irradiation of the entire desired cross-section. It can produce biomaterial with a high resolution compared to other systems [ 55 ]. DLP technology uses a digital projector as a light source, which significantly reduces the printing time and enables high-accuracy printing [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we concluded that primary cells from murine ovaries are not suitable for extrusion-based printing. To address this problem, photopolymerization-based bioprinting techniques, such as digital-light processing [45], show better performance in maintaining the cell viability when manufacturing artificial ovaries (data not shown).…”
Section: Discussionmentioning
confidence: 99%